Number of siblings and allergic rhinitis in children - Soewira Sastra; Lily Irsa; Muhammad Sjabaroeddin Loebis; Rita Evalina (Indonesian Pediatric Society, 2016)
Background Allergic rhinitis is one of the most common chronic diseases of childhood. Recent studies have suggested that having fewer siblings was associated with allergic rhinitis and atopic diseases in children. Previous studies also indicated that older siblings was associated with higher incidence of allergic rhinitis.Objectives To assess for a possible association between number of siblings and allergic rhinitis and to assess for an effect of birth order on allergic rhinitis in children.Methods We performed a cross-sectional study among school children aged 7 to 15 years, in the West Medan District from July to August 2011. Children with moderate or high risk of allergy were included. Subjects were divided into two groups, those with <3 siblings or â‰¥3 siblings. Children with acute respiratory tract infections, septal deviation, choanal atresia, nasal polyps, nasal tumors, or nasal foreign body were excluded. Risk of allergy was determined using the Indonesian Pediatrics Allergy Immunology Working Group trace card scoring system. Identification of allergic rhinitis and evaluation of its severity were done by use of the International Study of Asthma and Allergies in Childhood (ISAAC) core questionnaire. Allergic rhinitis was diagnosed based on history, physical examination, and anterior rhinoscopy.Results A total of 78 subjects were enrolled. Allergic rhinitis was significantly higher in children with <3 siblings than those with â‰¥3 siblings (OR 10.33; 95%CI 3.569 to 29.916). Furthermore, allergic rhinitis was significantly higher in first-born children than in their younger siblings (P=0.0001).Conclusion Larger number of siblings and non-first-born children are associated with lower incidence of allergic rhinitis in children.